Case Report: Fremitus Nystagmus in Superior Canal Dehiscence Syndrome - Morrison, Miranda; Korda, Athanasia; Wagner, Franca; Caversaccio, Marco Domenico; Mantokoudis, Georgios (Frontiers in Neurology, 2022)
Superior semicircular canal dehiscence is a structural bony defect of the roof of the superior semi-circular canal into the middle cranial fossa, responsible for the creation of a third window, which alters the dynamics of the inner ear. During humming, the vibratory waves entering the vestibulum and cochlea are re-routed through the dehiscence leading to a stimulation of the otolithic and ampullary vestibular organs. This is responsible for a torsional-vertical nystagmus known as ‘Fremitus Nystagmus’. In this case report, we video-document a rare case of Fremitus Nystagmus and its resolution after plugging of the superior semi-circular canal.